Tradisi Azan Ketika Memasuki Rumah Baru dalam Perspektif Hadis di Desa Klambir Lima Kampung - Khainur Arrasyid; Sulaiman Muhammad Amir (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study explores the tradition of calling the adhan when entering a new house in Klambir Lima Kampung Village, focusing on the religious, social, and cultural significance of the practice. Although there is no hadith that explicitly requires the adhan in a new house, this tradition is commonly carried out by the local community to seek blessings, spiritual protection, and peace. This study aims to analyze the religious basis of this tradition, its interpretation by scholars, and the social and psychological impacts it has on the residents of the house. Using a qualitative approach and case study method, this study examines the views of religious leaders, local communities, and Islamic scholars regarding the practice of adhan in new houses. Data collection was conducted through in-depth interviews, participant observation, and documentation studies, to provide a comprehensive understanding of the impact of this practice on social cohesion and individual spirituality. This study also investigates how this tradition relates to Islamic teachings, especially on the importance of dhikr and asking for protection from Allah. In addition, this study highlights the role of this tradition in strengthening social solidarity and cultural identity in the context of contemporary Islamic society. The research findings show that although this practice is not a religious obligation, it remains a meaningful and important custom, which strengthens individual faith and social relationships within the community. This study provides new insights into the relevance of local Islamic traditions in contemporary society, especially in preserving Islamic values ​​in the context of community culture. The hope is that these findings can encourage the development of a more contextual and tolerant approach to Islamic preaching, one that respects local wisdom and inspires younger generations to uphold spiritual values through cultural practices that align with Islamic principles.